Valorization of wastes from agrofood and pulp and paper industries within the biorefinery concept: southwestern Europe scenario - Romani, Aloia Perez (2018)
Nowadays, the need to attain a sustainable society increasingly demands for the development of an economy based on biorefineries. In Southwestern Europe, agrofood and forest industries produce significant amount of wastes that could satisfy the demand for renewable biomass to be used in a biorefinery scheme alternatively to traditional uses of these residues. This chapter will primarily cover the current scenario regarding the annual volume of residues generated by agrofood (cheese whey, vine pruning waste, and brewer's spent grains) and pulp and paper industry (sawdust, chips, bark, and sludge). Additionally, the present-day use and final destination of these wastes and their main environmental issues will be described and discussed; besides, advanced valorization strategies (e.g., fuels and chemicals) involving a biorefinery approach will be approached, based on current reports according to the chemical composition of each waste. Finally, new insights on valorization of wastes from agrofood and pulp and paper industries, its challenges, and trends for future research will be presented.